Dynamics of Communication Networks of Religious Educational Institutions and Broadcast Media in the Creative Industry - Fita Fathurokhmah; Ellya Pratiwi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
This study analyzes the dynamics of the communication network between the Islamic Communication and Broadcasting Study Program (KPI) of the Faculty of Da'wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta, and broadcasting media institutions, and identifies the obstacles faced in dealing with the creative industry. This study uses a qualitative approach. Data collection techniques include in-depth interviews and documentation. Data were analyzed using Rogers & Kincaid's communication network theory. The results of the study show that the communication network between the KPI Study Program and the broadcasting industry is still hierarchical, with a chain communication pattern that limits the flow of information and direct access of students to the industry. The main obstacles found include minimal opportunities for field practice, limited internship quotas, and a lack of industry involvement in developing a curriculum based on market needs. In addition, the formal cooperation that has been established between the Islamic Communication and Broadcasting Study Program and the broadcasting industry is still not optimal in creating a flexible and responsive communication system to the development of digital technology. This study recommends strengthening the academic-industry communication strategy through the development of more open communication patterns, such as star communication patterns, in order to increase direct interaction between students, lecturers, and the broadcasting industry. This effort is expected to strengthen the role of the KPI Study Program in producing graduates who are adaptive, innovative, and ready to compete in the creative and broadcasting industries.